Pendampingan Dan Pelatihan Desain Grafis Untuk Kewirausahaan Bagi Siswa SMK Muhammadiyah 9 Wagir - Arif Hidayatul Khusna; Mayang Dintarini (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
The problem faced by students is at the production stage, namely the problem of product labeling. Until now labeling was done simply or without labeling. If students can design their own product labels, of course this will add to the selling value of the product. The existence of labels and brochures also add value to the promotion of student products. The aim of this mentoring activity is to provide training and graphic design assistance to students of SMK. The steps of this community service activities are observations, socialization, graphic design training, assistance in making labels and brochures for student entrepreneurial products, as well as evaluating and reflecting on service activities. The result of this service activity was in the form of training and graphic design assistance for students. All of the activities was well done . This can be seen from the number of students who participated in training and mentoring for three days. In addition, there are positive responses from teachers and students that have an impact on the success of this graphic design training and assistance. This can be seen from the results of student designs that are attractive and can be used as a commercial tool.